2021
DOI: 10.1017/s0007114521000775
|View full text |Cite
|
Sign up to set email alerts
|

PPARγregulatesfabp4expression to increase DHA content in golden pompano (Trachinotus ovatus) hepatocytes

Abstract: N-3 long chain (≥C20) polyunsaturated fatty acids (LC-PUFA) are vital fatty acids for fish and humans. As a main source of n-3 LC-PUFA for human consumers, the n-3 LC-PUFA content of farmed fish is important. Previously, we identified fatty acid- binding protein (fabp)-4 as a candidate gene for regulating the n-3 LC-PUFA content. Herein, we further assessed the role of fabp4 in this process. First, a 2059 bp promoter sequence of fabp4 in Trachinotus ovatus was cloned and, using progressive deletion, determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…However, previous studies have shown that DHA and EPA could be natural PPAR agonist to activate PPARG signaling [29,30]. In golden pompano hepatocytes, the overexpression of PPARG increased the DHA content, whereas suppression of PPARG expression diminished this effect, suggesting that PPARG play an active role in regulating DHA content [31]. Here, we conducted the correlation analysis between PPARG and individual DHA-and EPAcontaining glycerophospholipid rather than total DHA or EPA content.…”
Section: Discussionmentioning
confidence: 95%
“…However, previous studies have shown that DHA and EPA could be natural PPAR agonist to activate PPARG signaling [29,30]. In golden pompano hepatocytes, the overexpression of PPARG increased the DHA content, whereas suppression of PPARG expression diminished this effect, suggesting that PPARG play an active role in regulating DHA content [31]. Here, we conducted the correlation analysis between PPARG and individual DHA-and EPAcontaining glycerophospholipid rather than total DHA or EPA content.…”
Section: Discussionmentioning
confidence: 95%
“…Only FABP4 and FABP5 are expressed across various cancer types, suggesting that genetic amplification itself is necessary but not sufficient for their abnormal expression in cancer. Expression of FABP4 , as a major target of PPARγ[ 19 ], has been shown to be controlled by PPARγ[ 4 ], and FABP4 has been shown to negatively regulate PPARγ expression level, likely through a negative feedback signaling loop. In contrast to FABP4 , FABP5 has been shown to facilitate fatty-acid induced PPARγ activation and downstream signaling, and activated PPARγ in turn upregulates FABP5 expression levels in prostate cancer[ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the family members including FABP4 , FABP5 , and FABP7 are abnormally expressed in cancer cells beyond tissue expression restriction and play important roles in cancer malignancy and progression[ 2 , 3 ]. FABP4 is normally expressed in adipocytes at high levels and its expression is controlled by peroxisome proliferator-activated receptor gamma (PPARγ)[ 4 ]. Accumulating evidence shows that FABP4 plays important roles in cancer progression in multiple cancer types, including breast cancer[ 5 ], ovarian cancer[ 6 ], and colon cancer[ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, FABP5 was higher in FO than in FLX placenta. FABPs have differential affinities to specific FAs: FABP5 binds to both DHA and AA, whereas FABP7 binds specifically to DHA [47,[52][53][54], and both FABP4 and FABP5 specifically increase the uptake of DHA [55][56][57][58]. Furthermore, although FABP3 was shown to bind preferentially to AA (n-6 FA) [54], it regulates both n-3 and n-6 FA transport in mouse trophoblasts [59].…”
Section: Maternal N-3 Fa Supplementation Affects the Placental Lipid ...mentioning
confidence: 99%